Fate of Ingested Aristolactams from Aristolochia Chilensis in Battus Polydamas Archidamas (Lepidoptera: Papilionidae) - Urzua-Moll, A; Santander-Meyer, R; Olguin-Gonzalez, A (2013)
We performed a sequestration study of aristolactams (ALs) from Aristolochia chilensis in Battus polydamas archidamas (Lepidoptera: Papilionidae) by examining the AL content of the plant, fifth instar larvae, osmeterial secretion, pupae, exuviae and feces. Aristolactam-I (AL-I) and aristolactam-II (AL-II) present in A. chilensis are sequestered by fifth instar larvae of B. polydamas archidamas. There is a preferential sequestration of AL-II, or a more efficient metabolization and excretion of AL-I, by the larva. No ALs were found in the osmeterial secretion, pupae and exuviae; in addition, little AL-I and no AL-II were found in larval frass. The two lactams, particularly AL-I, are extensively metabolized to other products in the larva. A reasonable hypothesis is that the ingested ALs are oxidized to their respective aristolochic acids. © 2013 by the authors; licensee MDPI, Basel, Switzerland.